Developing a modified mycological culture medium for Malassezia furfur by supplementing sabouraud dextrose agar with extracted lipid oil from egg yolk - Sivasinthujah, S.; Shalini, R.; Kannathasan, S.; Gnanakarunyan, T.J. (Mushroom Research Foundation, Thailand, 2026)
Malassezia furfur (M. furfur) is a lipophilic yeast that is associated with a variety of superficial and systemic dermatological conditions, including pityriasis versicolor, seborrheic dermatitis, and atopic eczema. Though it’s a clinically important etiological agent, in vitro research has been insufficient due to a lack of convenient culture media to isolate and subculture the organism. This study was aimed at developing a modified mycological culture medium for M. furfur by supplementing sabouraud dextrose agar (SDA) with extracted lipid oil from egg yolk. Malassezia furfur was isolated from Pityriasis versicolor patients attending Teaching Hospital Jaffna, in SDA with ghee (10%) media, and its presence was confirmed using microscopic, macroscopic, and biochemical examinations. Egg yolk oil was extracted by the solvent extraction method. SDA culture plates with different volumes of egg yolk oil (2x, x, x/2, x/4, x/8, and x/16; x refers to egg yolk oil extracted from one egg yolk) were streaked with confirmed colonies of M. furfur and incubated at 32 °C. Additionally, the optimal growth temperature and the impact of additives such as Na₂HPO₄, NaCl, and MgSO₄ were evaluated. Growth level (5-point scale), isolation, and isolated colony size (mm) were taken on the 3rd and 5th days of incubation. Furthermore, the growth of M. furfur in the modified culture medium, incorporating all optimized conditions, was assessed and compared with traditional agar formulations like SDA and SDA supplemented with ghee. The isolated colony size was reported as the mean and standard deviation (SD), and the data were subjected to examination by analysis of variance (ANOVA) (P<0.05) followed by Tukey’s test (α = 0.05) by using software, SPSS Statistics version 21.0. The volume of oil extracted from one egg yolk and the yield in of oil were 2 mL and 33.33 % respectively. Among the tested concentrations of egg yolk lipid oil, the x/8 was selected as the minimal volume required for optimal growth of M. furfur. The organism exhibited optimal growth at 32 °C. Furthermore, supplementation with Na₂HPO₄, NaCl, and MgSO₄ significantly enhanced growth. In the comparative study, the modified culture medium demonstrated better performance compared to the other existing culture media.
Keywords: Egg yolk oil; Lipophilic yeast; Malassezia furfur; Modified mycological culture media; Pityriasis versicolor; Solvent extraction